2017
DOI: 10.1140/epjc/s10052-017-5139-4
|View full text |Cite
|
Sign up to set email alerts
|

Charged thin-shell gravastars in noncommutative geometry

Abstract: In this paper we construct a charged thin-shell gravastar model within the context of noncommutative geometry. To do so, we choose the interior of the nonsingular de Sitter spacetime with an exterior charged noncommutative solution by cut-and-paste technique and apply the generalized junction conditions. We then investigate the stability of a charged thin-shell gravastar under linear perturbations around the static equilibrium solutions as well as the thermodynamical stability of the charged gravastar. We find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…In this section, we are interested in checking the stability of gravastars. For this purpose we define a new parameter η as the ratio of the derivatives of σ and P as follows: Övgün et al [122] used the above parameter which plays a fundamental role in determining the stability regions of the respective solutions of charged thin-shell gravastar model within the context of noncommutative geometry. Yousaf et al [123] also discussed the stability of the gravastar model in f (R, T ) gravity in the presence of charge.…”
Section: Stability Of the Gravastarmentioning
confidence: 99%
“…In this section, we are interested in checking the stability of gravastars. For this purpose we define a new parameter η as the ratio of the derivatives of σ and P as follows: Övgün et al [122] used the above parameter which plays a fundamental role in determining the stability regions of the respective solutions of charged thin-shell gravastar model within the context of noncommutative geometry. Yousaf et al [123] also discussed the stability of the gravastar model in f (R, T ) gravity in the presence of charge.…”
Section: Stability Of the Gravastarmentioning
confidence: 99%
“…They explored the dynamical stability of the transition layer for some specific cases and found that stable regions are enhanced near the formation of the expected event horizon. Lobo et al [15] explored the stability of gravastars related to the matter distribution in the transition layer.Övgün et al [16] constructed thin-shell gravastars in the background of noncommutative geometry and examined stability regions through radial perturbation about the equilibrium shell radius. Shamir and Ahmad [17] discussed various physical characteristics like, entropy, the EoS parameter, length of the shell, energy-thickness relation of the gravastar shell model in f (G, T ) gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Lobo and Garattini [14] investigated the stability of noncommutative thin-shell gravastar and found that stable regions must exist near the expected position of the event horizon. Övgün et al [15] developed thin-shell gravastar model from the matching of exterior charged noncommutative BH with interior DS manifold. They found that the developed structure follows the null energy condition and shows stable behavior for some suitable values of physical parameter near the expected event horizon.…”
Section: Introductionmentioning
confidence: 99%